A proposed concept based on the viewpoint of education experts for the development of secondary education in Iraq - Mahmood, Majid Ayoub (Journal of Educational and Psychological Sciences, 2020)
The aim of this research is to present a proposed concept based on the viewpoint of education experts for the development of secondary education in Iraq. The researcher sought to get acquainted with its reality and identify the problems which faces. The descriptive analytical methodology had been used, where the research tool as a questionnaire consisted of (30) items distributed in five areas: school buildings and equipment, curriculum and teaching methods, teaching staff preparation and training, evaluation and exams, and students. The research questionnaire sample consisted of a group of experts who were chosen intentionally, amounting to (50) experts. Those who were of scientific positions, experts in secondary education and those who practiced education and supervision in the secondary schools and university levels, for a period of nearly (40) years. Moreover, their experiences were in various universities and governorates. The results of the research revealed that the mathematical averages at the device field reached (4.32), at the level of buildings and educational equipment reached (4.35), the field of curriculum and teaching methods as well as the field of teachers (4.41), meanwhile the field of evaluation and exams reached (4.35) and the field of students got (4.12). Based on these obtained results, this perception concept has been proposed for the development of secondary education in Iraq. The researcher suggested conducting other studies to benefit from the experiences of countries that fought similar recent wars, to show how to overcome their crises. Finally, the researcher recommended applying the proposed methodology on the teacher’s side, first of all being the cornerstone of the educational process.
Keywords: proposed concept; Education development; Iraq